2019
DOI: 10.1177/1559325819847834
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a Cancer Co-Initiator: New Mechanistic Model Predicts Low/Negligible Risk at Noninflammatory Carcinogen Doses

Abstract: Linear-no-threshold (LNT) risk extrapolation has long been applied to estimate risks posed by low-level environmental carcinogen exposures, based on the 60-year-old multistage somatic mutation/clonal expansion (MSM) cancer theory. Recent evidence supports an alternative theory: Malignant tumors arise most efficiently from a stem cell that incurs requisite mutations and also is activated by inflammation to an epigenetically mediated and maintained state of adaptive hyperplasia (AH). This new inflammation-MSM (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
(114 reference statements)
0
22
0
Order By: Relevance
“…Virchow studied the four signs of inflammation (redness, swelling, heat and pain) and hypothesized a link between microinflammation and subsequent tumor progression ( Heidland, Klassen, Rutkowski, & Bahner, 2006 ). Experimental studies have indeed confirmed that inflammation can stimulate or induce tumor initiation, growth, and metastasis ( Bogen, 2019 ; Chang et al, 2019 ; Coussens & Werb, 2002 ; Fishbein et al, 2020 ; Gartung et al, 2019 ; Gilligan et al, 2019 ; Guerra et al, 2007 ; Mantovani et al, 2008 ; Panigrahy et al, 2019 ; Sulciner et al, 2018 ; Wang & Dubois, 2010 ). Cancers arise frequently at sites of chronic inflammation and injury as the observation that secondary tumors occur at the points of injury (e.g.…”
Section: Inflammation and Cancermentioning
confidence: 93%
See 4 more Smart Citations
“…Virchow studied the four signs of inflammation (redness, swelling, heat and pain) and hypothesized a link between microinflammation and subsequent tumor progression ( Heidland, Klassen, Rutkowski, & Bahner, 2006 ). Experimental studies have indeed confirmed that inflammation can stimulate or induce tumor initiation, growth, and metastasis ( Bogen, 2019 ; Chang et al, 2019 ; Coussens & Werb, 2002 ; Fishbein et al, 2020 ; Gartung et al, 2019 ; Gilligan et al, 2019 ; Guerra et al, 2007 ; Mantovani et al, 2008 ; Panigrahy et al, 2019 ; Sulciner et al, 2018 ; Wang & Dubois, 2010 ). Cancers arise frequently at sites of chronic inflammation and injury as the observation that secondary tumors occur at the points of injury (e.g.…”
Section: Inflammation and Cancermentioning
confidence: 93%
“…Carcinogens may induce a specific gene mutation frequently observed in a particular cancer increasing the risk of cancer ( Moore et al, 2008 ). While carcinogen-induced DNA damage can cause cancer, some studies suggest that DNA adducts alone or mutations alone may not be sufficient to cause cancer ( Bogen, 2019 ; Johnson et al, 2014 ). Non cell-autonomous mechanisms such as inflammation and angiogenesis may also be critical to tumor initiation and progression ( Folkman, 2007 ).…”
Section: Carcinogens and Inflammationmentioning
confidence: 99%
See 3 more Smart Citations